2008
DOI: 10.2147/vhrm.s2240
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of calculated future cardiovascular disease by monocyte count in an asymptomatic population

Abstract: Introduction:Although atherogenesis is clearly entwined with systemic infl ammation, the risk-predictive relationship between preclinical and overt cardiovascular disease (CVD) and systemic white blood cell (WBC) subtypes remains unclear. Implication of an association would greatly facilitate cardiac risk prediction, assessment and monitoring. Methods: 1383 asymptomatic individuals (795 men, 588 women) attending for executive health screening were examined clinically as well as with phlebotomy and exercise str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 25 publications
1
17
0
2
Order By: Relevance
“…13 Haemopoietic progenitors might accumulate in the circulation and the spleen and are thus poised to potentiate leucocyte supply by establishing extramedullary haemopoiesis. [34][35][36] In mice, bone-marrowderived monocytes released in response to variable stress or to stressful events (such as myocardial infarction) migrate to the arterial wall, where they instigate atherosclerotic infl ammation. 11,13,37 Results from animal studies 38 point to increased haemopoiesis and arterial infl ammation as important mechanisms in stress.…”
Section: Discussionmentioning
confidence: 99%
“…13 Haemopoietic progenitors might accumulate in the circulation and the spleen and are thus poised to potentiate leucocyte supply by establishing extramedullary haemopoiesis. [34][35][36] In mice, bone-marrowderived monocytes released in response to variable stress or to stressful events (such as myocardial infarction) migrate to the arterial wall, where they instigate atherosclerotic infl ammation. 11,13,37 Results from animal studies 38 point to increased haemopoiesis and arterial infl ammation as important mechanisms in stress.…”
Section: Discussionmentioning
confidence: 99%
“…3 The monocyte count is positively associated with body mass index (BMI) and triglycerides (TG) and is negatively related to high-density lipoprotein cholesterol. 4 Furthermore, clinical studies report that the monocyte count is also associated with subclinical peripheral atherosclerosis [5][6][7] and the development of cardiovascular disease. 4 Overall, it is proposed that the mononuclear phagocyte system contributes to the pathophysiology of cardiometabolic diseases (review in 8 ).…”
Section: Conclusion-this Work Demonstrates a Major Impact Of Fat Massmentioning
confidence: 99%
“…Clinical studies have demonstrated that monocytes play a key role in atherosclerosis [6,7], myocardial infarction (MI) [8], and healing after MI [9]. Monocytes are attracted to the coronary artery wall, where they differentiate to macrophages, become loaded with lipids, and remain trapped there.…”
Section: Introductionmentioning
confidence: 99%